COP21 Africa Pavilion side event: Taking Forward the Implementation of National Climate-Smart Agriculture Programmes in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This event provided an opportunity to dialogue on the appropriate policy and financing mechanism to scale-up the adoption of climate-smart agriculture (CSA) practices in defined farming systems in Africa. The event built on experiences drawn from “supporting preparation of country CSA programs in five countries in eastern and southern Africa†). Photo credit: V. Atakos (CCAFS)